Europeans abroad, 1450-1750 - Ringrose, David R. (Exploring world history., 2018)
"Ringrose looks beyond the traditional history of European expansion, which highlights European conquests, empire building, and hegemony, in order to explore the more human and genuinely cross-cultural dimensions of Europeans abroad before 1750"--